Activity of Ricinus communis (Euphorbiaceae) and ricinine against the leaf-cutting ant Atta sexdens rubropilosa (Hymenoptera : Formicidae) and the symbiotic fungus Leucoagaricus gongylophorus - Bigi, MFMA; Torkomian, V. L.; de Groote, S. T.; Hebling, MJA; Bueno, O. C.; Pagnocca, F. C.; Fernandes, J. B.; Vieira, P. C.; da Silva, MFGF (Wiley-Blackwell, 2004)
The focus of this study was the identification of compounds from plant extracts for use in crop protection. This paper reports on the toxic activity of fractions of leaf extracts of Ricinus communis L (Euphorbiaceae) and isolated active compounds in the leaf-cutting ant Atta sexdens rubropilosa Forel and its symbiotic fungus Leucoagaricus gongylophorus (Singer) Moller. The main compounds responsible for activity against the fungus and ant in leaf extracts of R communis were found to be fatty acids for the former and ricinine for the ants. (C) 2004 Society of Chemical Industry.
Keywords: insecticidal activity; antifungal activity; Atta sexdens rubropilosa; Leucoagaricus gongylophorus; Ricinus communis; ricinine